Pengaruh Harga, Kualitas Produk, Variasi Produk, Live Streaming Selling Terhadap Keputusan Pembelian Fashion Pada Toko Alva Store di Labuhanbatu - Handayani, Mey Lena; Prayoga, Yudi; Hendry, Raja Saul Marto (Universitas Labuhanbatu, 2025)
This study aims to analyze the effect of price, product quality, product variety, and live streaming selling on fashion purchasing decisions. Poor quality products can reduce brand awareness and hamper purchasing decisions. The research methodology used a quantitative approach by distributing questionnaires to fashion consumers in Labuhanbatu. The data obtained were analyzed using multiple regression techniques to identify the extent to which each independent variable affects financial behavior. Price, product quality, product variety, and live stream selling all have a positive and significant influence on purchasing decisions. Product quality has the strongest influence, followed by product variety, live streaming selling, and price. This suggests that these factors must be considered and managed properly to improve consumers ' purchasing decisions. The value of R Square .852 indicates that 85.2% of the variation in purchase decisions can be explained by these four variables. This suggests that the model has excellent predictive capabilities.